A Review on the Performance of the Nanofluid Based Solar Collectors - Solar Energy - Sharma, Kapil; Singh, Satnam; Yadav, Manvendra; Yadav, Sanjay; Tripathi, Naveen Mani (Asian Review of Mechanical Engineering, 2019)
Using nanofluids as an innovative kind of liquid blend with a trivial volume fraction (in percent) of nanometer-sized solid particles in suspension is a fairly a novel arena or idea. The objective of this presented review paper is to inspect the performance of the nanofluid-based solar collector (NBSC). In past few years for a number of experimental and industrial thermal engineering systems solar energy has proven to be the best input energy source. The scarcity of fossil fuels and environmental contemplations motivated the researchers to utilize alternative energy sources such as solar energy, wind energy, tidal energy etc. Therefore, it is essential to boost the performance of the solar thermal engineering systems. Because of better rheological properties nanofluids are utilized to build up the performance of conventional solar thermal engineering systems. Therefore, major part of this presented review paper lays a main emphasis to investigate the effects of nanofluids on the performance of solar collectors. Some proposals are also given to use the nanofluids for future work in different solar thermal engineering systems such as parabolic trough systems (PTS), solar thermoelectric cells and finally, the challenges of using nanofluids in solar energy devices are reviewed in brief.